Objective Evaluation of Relationship Between Tear Film Stability and Visual Fatigue [Letter] - Bandyopadhyay A; Jaman F; Chaurasiya SK (Clinical Optometry)
Ankita Bandyopadhyay,1 Firdoos Jaman,2 Suraj Kumar Chaurasiya3 1Department of Optometry, School of Allied and Healthcare Science at Centurion University, Bhubaneswar, India; 2Department of optometry, Regional Institute of Paramedical and Nursing Sciences (RIPANS), Aizawl, Mizoram, India; 3Department of Optometry and Vision Science, CL Gupta Eye Institute, Moradabad, IndiaCorrespondence: Suraj Kumar Chaurasiya, CL Gupta Eye Institute, Ram Ganga Vihar Phase II, Moradabad, 244001, India, Email csurajk414@gmail.com